Fifty Materials That Make the World - Baker, Ian (Springer International Publishing, 2018)
This book introduces materials and how advances in materials result in advances in technology and our daily lives. Each chapter covers a particular material, how the material was discovered or invented, when it was first used, how this material has impacted the world, what makes the material important, how it is used today, and future applications. The list of materials covered in this book includes stone, wood, natural fibers, metals, clay, lead, iron, steel, silicon, glass, rubber, composites, polyethylene, rare earth magnet, and alloys. .